1996
DOI: 10.1021/bi961251g
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Conformation and Dynamics:  A Red Edge Excitation Shift Study

Abstract: The fluorescence emission maximum of a polar fluorophore in viscous medium often shows a dependence on excitation wavelength, a phenomenon which is named red edge excitation shift (REES). We have found that the fluorescence spectra of the tubulin tryptophans exhibit a REES of about 7 nm. Also, their steady state fluorescence polarization and mean lifetimes show a dependence on both excitation and emission wavelengths. These results indicate that the average tryptophan environment in tubulin is motionally restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 54 publications
6
66
3
Order By: Relevance
“…Calculated site energies using a dielectric constant value of 8.41 range between 35 888 and 36 276 cm 21 , giving the maximum energy difference between Trps of 388 cm 21 . These site energies are shown in figure 1c and is there a significant delocalization over more than one pigment, with meaningful contributions between Trps 4 and 7, and Trps 2 and 3, owing to the close site energies between these pigments and their relatively large couplings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculated site energies using a dielectric constant value of 8.41 range between 35 888 and 36 276 cm 21 , giving the maximum energy difference between Trps of 388 cm 21 . These site energies are shown in figure 1c and is there a significant delocalization over more than one pigment, with meaningful contributions between Trps 4 and 7, and Trps 2 and 3, owing to the close site energies between these pigments and their relatively large couplings.…”
Section: Resultsmentioning
confidence: 99%
“…These are comparable to the room temperature fluorescence quantum yields of bacteriochlorophyll of 0.18, and the yield for LH1 of 0.08 and LH2 of 0.10 [20], respectively. The 'red edge effect' has also been observed in tubulin [21] indicating Trp to Trp energy transfer [22]. Thus, these may serve as potential conduction pathways in tubulin and microtubules [23].…”
Section: Introductionmentioning
confidence: 90%
“…Wavelength-selective fluorescence has been previously applied for monitoring protein dynamics and conformation in solution 19,[67][68][69][70][71] as well as in more complex systems such as the intact eye lens. 72, 73 We have previously applied this approach for studying organization and dynamics of membrane-bound probes and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The tryptophan residue in these cases is exposed to aqueous environment undergoing much faster solvent relaxation as compared to the fluorescence lifetimes of the concerned tryptophans. It is for this reason that tryptophans in denatured proteins do not exhibit REES, e.g., tubulin 77 (see later). However, considerable REES effects were observed for many proteins (such as tetrameric form of melittin, human serum albumin, albumin complexed with sodium dodecyl sulfate) with intermediate maxima of emission (between 325 and 341 nm).…”
Section: Soluble Proteinsmentioning
confidence: 99%
“…80 The REES approach has been used in a number of cases to monitor the tryptophan environment and dynamics in proteins such as human α 1 -acid glycoprotein, 81 bothropstoxin-I from the venom of Bothrops jararacussu, 82 ascorbate oxidase, 83 smooth muscle myosin light chain kinase, 84 skeletal myosin rod, 85 the human leukocyte antigen complex, 86 and the pore-forming α-toxin from Staphylococcus aureus. 87 In addition, it has been shown that the environment of tryptophans in cytoskeletal proteins such as tubulin 77 and spectrin 88,89 are motionally restricted and display REES. Importantly, observation of REES in multitryptophan proteins considerably rules out the possibility of homotransfer among tryptophans.…”
Section: Soluble Proteinsmentioning
confidence: 99%